ONLINE SPACES, IMPOSSIBLE IMAGINARIES, AND SYNTHETIC SOCIALITY - Sinnreich, Aram; John, Nicholas (AoIR Selected Papers of Internet Research, 2023)
Social media enable the formation of unprecedented numbers of ties, and allow for communication at an unprecedented scale. Features such as unfriending and muting on the one hand, and favoriting and “close friends” on the other, enable users to manage this abundance, allowing them to silence certain voices and to enhance certain others. These features create situations that sometimes cannot be mapped onto familiar offline scenarios. We argue that these new, sui generis situations instantiate a set of social architectures and imaginaries that we describe collectively using the term, synthetic sociality. We analogize these synthetically social situations with Derrida’s concept of écriture, through which written language is understood not as a derivative reflection of orality, but rather as a self-contained set of communicative capacities that precedes and surrounds oral communication. To exemplify the concept of synthetic sociality, we present three forms of “born digital” social transactions: the “block” feature in Facebook (which can create a situation in which not all parties to a conversation see the entirety of the conversation), the “restrict” feature in Instagram (in which a user can respond to a post though, unbeknownst to them, they have no audience), and “favorite” contacts in address book apps (which allow for their messages to rise to the top of the inbox). In none of these cases are the resulting social architectures easily analogized to those achievable in a physical social environment, crucially because at least one party to these synthetically social situations lacks full knowledge of it.